Parameterized Design of Female Chest Shape Based on UG-platform (Journal of Fiber Bioengineering and Informatics, 2018)
This study aims to provide technical platform for parameterized design female body model with differentchest shapes. Initially, the characteristic parameters, curves and points of female chest shape weredeveloped based on analysis of the features of female chest shapes. Then, these parameters were appliedto make parameterized representation of the female chest characteristic points' coordinate; Parametersspline curve formulas were used to generate chest characteristic curves and the chest of parameterizedmodelling was realized. Furthermore, the parameterized modelling procedures of female chest weredeveloped using development tools UG/Open, which could get different female chest shapes by inputtingdifferent parameter values.
Keywords: Female Chest; Characteristic Parameter; Parameterized Design; UG Platform